2009
DOI: 10.1143/jjap.48.011301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Transfer Characteristics of Amorphous InGaZnO4 Thin-Film Transistors

Abstract: The transfer characteristics of amorphous InGaZnO 4 thin-film transistors (a-IGZO TFTs) were measured at temperatures ranging from 298 to 523 K in order to analyze the behavior of the above-threshold (ON state) and subthreshold regions. For comparison, the transfer characteristics of a hydrogenated amorphous silicon TFT (a-Si:H TFT) were measured in the same temperature range. We developed a simple analytical model that relates the threshold voltage (V t ) decrease due to increasing temperature to the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 23 publications
4
90
0
Order By: Relevance
“…Negative V TG shows an increment of saturation mobility with increasing temperature, due to the increment of free carrier concentrations by thermal excitation to the conduction band from localized states. 10,11,13 This trend is commonly observed in SG a-IGZO TFTs, while the Fermi level falls inside or below the tail states. 11 On the other hand, positive V TG shows an opposite trend on temperature dependent saturation mobility.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Negative V TG shows an increment of saturation mobility with increasing temperature, due to the increment of free carrier concentrations by thermal excitation to the conduction band from localized states. 10,11,13 This trend is commonly observed in SG a-IGZO TFTs, while the Fermi level falls inside or below the tail states. 11 On the other hand, positive V TG shows an opposite trend on temperature dependent saturation mobility.…”
Section: Introductionmentioning
confidence: 58%
“…The temperature dependent characteristics of SG a-IGZO TFTs has been investigated by many groups to understand the conduction mechanism. [10][11][12] In this paper, we investigated the top gate voltage dependent transfer characteristics measured at bottom gate terminal and temperature (from 25 to 70 o C) dependency in DG a-IGZO TFTs. The temperature dependent transfer characteristics were measured for top gate biased (V TG ) -20, 15,-10, -5, 0, +5, +10, +15 and +20V sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 shows the luminance L M (T ) as a function of temperature T , relative to the luminance L M (20 • C) at 20…”
Section: A Luminancementioning
confidence: 99%
“…6) Notably, these papers reported that the chemical composition of the IGZO films is not stable, and there are still reliability problems in the interface zone of devices. 7) Both the composition and annealing temperature of IGZO thin films affect the film resistance and interface problems, 57) so stable IGZO thin film characteristics were obtained by using the co-sputtering system to deposit thin films and the samples were annealed with different depositing oxygen flow rates. 8,9) In fact, most single thin film systems have better electrical properties after an annealing treatment at 675 875 K for 12 h. For a double layer structure, high temperature annealing always decreases the reliability in the interface zone due to interface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) In fact, most single thin film systems have better electrical properties after an annealing treatment at 675 875 K for 12 h. For a double layer structure, high temperature annealing always decreases the reliability in the interface zone due to interface diffusion. 7,9,10) Electrical current testing is a low temperature process carried out in atmosphere. 11) Its mechanism is an electrical current induced crystallization (EIC) 12,13) that has been largely ignored in the optoelectronic thin films until now.…”
Section: Introductionmentioning
confidence: 99%